2013
DOI: 10.1063/1.4802722
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced structural phase transition in solid oxidizer KClO3: A first-principles study

Abstract: High pressure behavior of potassium chlorate (KClO3) has been investigated from 0 to 10 GPa by means of first principles density functional theory calculations. The calculated ground state parameters, transition pressure, and phonon frequencies using semiempirical dispersion correction scheme are in excellent agreement with experiment. It is found that KClO3 undergoes a pressure induced first order phase transition with an associated volume collapse of 6.4% from monoclinic (P2(1)/m) → rhombohedral (R3m) struct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
(108 reference statements)
2
11
0
Order By: Relevance
“…Since MNO 3 nitrates contain molecular complexes (nitrate anions, NH 4 cations), it is important to take into consideration the weak intermolecular Van der Waals interactions. DFT can predict the properties of the energetic materials that are in close agreement with experiments provided the exchange-correlation functionals are corrected to describe the weak intermolecular interactions [7,[42][43][44][45][46][47][48]. Thus, in comparison with to the LDA and GGA [49] results , G. Vaitheeswaran et al [7] found that the crystal structure of alkali-metal nitrates is well described by the dispersion-corrected functional DFT-D [50].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Since MNO 3 nitrates contain molecular complexes (nitrate anions, NH 4 cations), it is important to take into consideration the weak intermolecular Van der Waals interactions. DFT can predict the properties of the energetic materials that are in close agreement with experiments provided the exchange-correlation functionals are corrected to describe the weak intermolecular interactions [7,[42][43][44][45][46][47][48]. Thus, in comparison with to the LDA and GGA [49] results , G. Vaitheeswaran et al [7] found that the crystal structure of alkali-metal nitrates is well described by the dispersion-corrected functional DFT-D [50].…”
Section: Introductionmentioning
confidence: 72%
“…So, as regards transition pressure P tr , unfortunately, its adequate theoretical evaluation is impossible without calculation of vibrational structure. In contrast to KClO 3 [44], transition pressure for KNO 3 is relatively small [33,37]. Credibility of theoretical predictions of the pressure induced structural phase transitions using the pressure dependences of enthalpy H (P) = E + PV can be sufficiently high for the relatively high external pressure P >> 3kTN/(2V) [68], kthe Boltzmann constant, N-number of atoms.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Potassium perchlorate is, in turn, decomposed to yield potassium chloride and oxygen [12,13]. In the process of the thermal decomposition of KClO 3 , absorption of heat increases the diffusion speed and vibration amplitude of the crystals, causing cleavage and reformation of the Cl−O bonds in KClO 3 with subsequent formation of stable KClO 4 .…”
Section: Introductionmentioning
confidence: 99%